Pengaruh Kepemimpinan Instruksional, Disiplin Kerja dan Konflik Kerja Terhadap Kinerja Guru MTsN 1 Blitar - Eryda Sochifu; Nisa Mutiara; Eka Askafi (Universitas Islam Kadiri, 2023)
In the Decree of the Minister of Religion 633 of 2020 concerning Bureaucratic Reform of the Ministry of Religion, it is stated that one of the programs is Human Resources which aims to create clean, professional and responsible apparatus through employee management by implementing a competency-based Human Resources management system. The research objective is a description of the answer you want to know, Sugiyono revealed that the research objective is so that data can be found, developed, and proven. Meanwhile, the results of the research will obtain new knowledge so that it can be used to understand, solve, and anticipate problems. The purpose of this research is to analyze the simultaneous influence of instructional leadership, work discipline and work conflict on teacher performance at Madrasah Tsanawiyah Negeri 1 Blitar. Based on the problems discussed in this study, the researcher used a quantitative approach, the value of the Anova F Test: 53,286 with Sig F Test: 0.000 <0.05 So there is a simultaneous influence of the independent variables on the dependent variable or H0 is rejected and H1 is accepted. Sig. Value the value of R Square and adjusted R Square, if it is close to 1, the greater it can explain the dependent variable (Y). The R value or multiple correlation is 0.857, the R Square is 0.734 with the Adjusted R Square value: 0.720 > 0.5 indicating that a set of independent variables can strongly explain the dependent variable, and is significant because the simultaneous test rejects H0. The magnitude of the effect is 72%, and the remaining 100% -72% = 28% is explained by other variables outside the model.